Workflow patterns and potential for optimization in endovascular stroke treatment across the world: results from a multinational survey. (6th April 2020) - Ospel, Johanna Maria; Almekhlafi, Mohammed A; Menon, Bijoy K; Kashani, Nima; Chapot, René; Fiehler, Jens; Hassan, Ameer E; Yavagal, Dileep; Majoie, Charles B L.M; Jayaraman, Mahesh V; Hill, Michael D; Goyal, Mayank
Abstract : Background: The benefit of endovascular treatment (EVT) is highly time-dependent, and treatment delays reduce patients' chances to achieve a good outcome. In this survey-based study, we aimed to evaluate current in-hospital EVT workflow characteristics across different countries and hospital settings, and to quantify the time-savings that could be achieved by optimizing particular workflow steps. Methods: In a multinational survey, neurointerventionalists were asked to provide specific information about EVT workflows in their current working environment. Workflow characteristics were summarized using descriptive statistics and stratified by country and physician characteristics, such as age, career stage, personal and institutional caseload. Results: Among 248 respondents from 48 countries, pre-notification of the neurointerventional team was used in 70% of cases. The emergency department (ED) and CT scanner, and the CT scanner and neuroangiography suite, were on different floors in 23% and 38%, respectively. Redundant procedures in the ED were often routinely performed, such as chest x-rays (in 6%). General anesthesia was the most frequently used anesthesia protocol for EVT (42%), and an anesthesiologist was available in 82% for this purpose. 52% of the participants used a pre-prepared EVT kit. Conclusion: The current structure of EVT workflows offers possibilities for improvement. While some bottlenecks, such as the spatial department set-up, cannot easily be resolved, pre-notification tools and pre-prepared EVT kits are more straightforward to implement and could help to reduce treatment delays, and thereby improve patient outcomes.